Theoretical Study of Retinol, Niacinamide and Glycolic Acid with Halloysite Clay Mineral as Active Ingredients for Topical Skin Care Formulations - Ana Borrego-Sánchez; Claro Ignacio Sainz-Díaz; Luana Perioli; César Viseras (Molecules, 2021)
The adsorption of retinol, niacinamide and glycolic acid active ingredients on the internal surface of halloysite in an aqueous environment was explored at the molecular level by means of calculations based on quantum mechanics and force fields from empirical interatomic potentials. These active ingredients are stably adsorbed on the internal surface of halloysite forming hydrogen bonds between the hydrogen, oxygen and nitrogen atoms with the hydroxyl groups of the inner surface of the halloysite. In addition, electrostatic interaction between these active ingredients with the water molecules was observed. Therefore, the theoretical results indicate that the adsorption of these active principles is favourable in the halloysite nanotube, which allows directing future experimental investigations for the development and design of retinol, niacinamide and glycolic acid with halloysite nanotubes systems, which may be topical formulations for skincare.